2007
DOI: 10.1167/iovs.07-0068
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Genetics of Leber's Congenital Amaurosis: A Multicenter Study of Italian Patients

Abstract: RPE65 gene mutations represented a significant cause of LCA in the Italian population, whereas GUCY2D and CEP290 mutations had a lower frequency than that found in other reports. This finding suggests that the genetic epidemiology of LCA in Italy is different from that reported in the United States and in northern European countries. Autofluorescence in patients with RPE65 mutations was more frequently associated with preserved retinal thickness, which suggests that these mutations are not associated with prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
104
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 40 publications
12
104
0
6
Order By: Relevance
“…Because each blade of the propeller structure contributes a residue to the iron ion coordination system, substitutions in any sheet could displace the respective critical residue leading to disruption of iron ion binding. Missense mutations that result in substitutions of either the first or second shell iron ion ligands have been found in LCA patients (37)(38)(39), consistent with biochemical studies that demonstrated both first and second shell iron ion ligands are essential for RPE65 isomerase activity (4,40).…”
Section: Rpe65 In Retinal Diseasessupporting
confidence: 77%
“…Because each blade of the propeller structure contributes a residue to the iron ion coordination system, substitutions in any sheet could displace the respective critical residue leading to disruption of iron ion binding. Missense mutations that result in substitutions of either the first or second shell iron ion ligands have been found in LCA patients (37)(38)(39), consistent with biochemical studies that demonstrated both first and second shell iron ion ligands are essential for RPE65 isomerase activity (4,40).…”
Section: Rpe65 In Retinal Diseasessupporting
confidence: 77%
“…In agreement with previous imaging studies (Simonelli et al 2007;Pasadhika et al 2010), Jacobson et al (2013) report that LCA1 patients retain normal photoreceptor laminar architecture aside from foveal cone outer segment abnormalities and, in a few patients, foveal cone loss. Outer nuclear layer and photoreceptor outer segment thickness measurements in the rod-dominant retina (i.e., outside the fovea) were normal in all patients evaluated.…”
Section: Patient Characterizationsupporting
confidence: 92%
“…Histopathological analysis of two postmortem retinas (a 26-wk-old preterm abortus and a 12-yr-old donor) revealed signs of photoreceptor degeneration in both rods and cones Porto et al 2003). Later studies using state of the art, in-life imaging (i.e., optical coherence tomography) revealed no obvious degeneration in patients as old as 53 years of age (Simonelli et al 2007;Pasadhika et al 2010).…”
Section: Patient Characterizationmentioning
confidence: 95%
“…LCA1 patients present in infancy with severely impaired vision and extinguished ERG despite a normal fundus and retained photoreceptors in both their macular and peripheral retina for decades. [39][40][41][42] There is relatively better maintenance of retinal structure in LCA1 patients than that seen in other forms of the disease. 42 Taken together, this suggests an important role for the zebrafish as an animal model on which rapid visual screening and retinal histology may offer a unique advantage in the study of GC1 disease through both gene knockdown or future studies of dominant gene supplementation.…”
Section: Discussionmentioning
confidence: 99%